1973
DOI: 10.1037/h0035215
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive responses to stress: Effects of changes in demand and sex.

Abstract: Clinical observations and previous experimental work suggest that increased intrusive and repetitive thought after exposure to stressful events is a cognitive response tendency that occurs in general population groups. Tins replication study content analyzed subjects' reports of mental contents before and after neutral and stress films. Data were contrasted for male and female subject samples and for different instructional demands. The data show that the stress film exerted a significant influence on increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…In summary, we still know very little about sex differences in the course of sympathetic arousal after provocation. Although it may appear from these studies that significant differences would be found in better designed and more systematic studies, other studies of reaction to nonaggressive stress have shown no sex differences in verbal reaction or in a variety of physiological and behavioral measures (Becker, Horowitz, & Campbell, 1973;Neufeld & Davidson, 1974). Also, Harris and Huang (1974) found no sex differences in a study that varied attributions given to angered subjects for the cause of arousal.…”
Section: Physiological Concomitants Oj Reaction To Provocationmentioning
confidence: 66%
“…In summary, we still know very little about sex differences in the course of sympathetic arousal after provocation. Although it may appear from these studies that significant differences would be found in better designed and more systematic studies, other studies of reaction to nonaggressive stress have shown no sex differences in verbal reaction or in a variety of physiological and behavioral measures (Becker, Horowitz, & Campbell, 1973;Neufeld & Davidson, 1974). Also, Harris and Huang (1974) found no sex differences in a study that varied attributions given to angered subjects for the cause of arousal.…”
Section: Physiological Concomitants Oj Reaction To Provocationmentioning
confidence: 66%
“…There are clearly many connections between the experience of having a song stuck in one’s head and other involuntary thoughts (Beaman & Williams, 2010; Hyman et al, 2013). The research methods for studying stuck songs are based on the traumatic film method of creating involuntary thoughts (Antrobus, Singer, & Greenberg, 1966; Becker, Horowitz, & Campbell, 1973; Holmes & Bourne, 2008; Horowitz & Becker, 1971a, 1971b; Horowitz, Becker, & Moskowitz, 1971; Hyman et al, 2013) and the diary methods of investigating involuntary memories (Berntsen, 1996; Kvavilashvili & Mandler, 2004; Mace, 2005). The convergence of findings reveals that although stuck songs are a special form of involuntary thought, they share features with other instances of failing to control the contents of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Affective responses to stress include negative affect (e.g., feelings of tension, panic, feeling overwhelmed, irritability, restlessness, anger, guilt, sadness, grief, and depression) or positive affect (e.g., feelings of happiness, enthusiasm, contentment, and excitement; Zhaoyang et al, 2020 ). Cognitive responses to stress include mental slowing, confusion, narrowing of focus, difficulty concentrating, memory impairment (forgetfulness), increased or decreased awareness of one’s surroundings, general negative thinking, intrusive and repetitive thoughts and images, constant worry, difficulty making decisions, poor abstract thinking, disturbed thinking, difficulty identifying familiar objects or people, loss of orientation in time and place, and changes in learning and memory ( Becker et al, 1973 ; Bryce, 2001 ; Kemeny, 2003 ).…”
Section: Introductionmentioning
confidence: 99%